CONCEPT OF SACRAL ANTHROPOLOGY IN THE STRUCTURE OF THE BIBLICAL HERMENEUTICS OF GREGORY SKOVO- RODA AS A MEANS OF EDUCATING THE PERSONALITY SPIRITUALITY - Левченко, Наталія (New Collegium, 2020)
The basic challenges and criteria of spiritual education of students are determined. it was emphasized that the works of Ukrainian literature, in particular the sentimental novels and short stories of Gregory Skovoroda, play an important role in the system for concluding a scale of universal human values. it is noted that the artistic text encourages spiritual purification. The research is devoted, as well, to the study art model of sacredly man in Ukrainian prose of Baroque. it is taken to the dichotomy sensely horizontal line, which combines in itself celestial and earthly, eternal and mortal, spiritual and corporal, sainted and sinful it is taken to the dichotomy sensely horizontal line, which combines in itself celestial and earthly, eternal and mortal, spiritual and corporal, sainted and sinful.